Further Observations on the Occurrence of ‘Teeth’ in the Dog-Whelk Nucella Lapillus - Crothers, J. H. (Journal of the Marine Biological Association of the United Kingdom, 1971)
The formation of ‘teeth’ in immature Nucella lapillus (L.) is indicative of a stoppage in growth. Along the western coasts of southern Britain the proportion of individuals showing these growth disturbances is predictably related to the exposure of the shore to wave action. Farther east the proportion is much higher but not obviously so related. Sharp discontinuities separate eastern and western populations. Possible reasons for the differences are discussed and it is concluded that great care must be exercised when applying information about this species derived from the one coast to situations on the other. The potential value of this species as an indicator of environmental change is considered.